An Integrated Planning Framework for the Development of Sustainable and Resilient Cities – The Case of the InSMART Project. (2017) - Gargiulo, M.; Chiodi, A.; De Miglio, R.; Simoes, S.; Long, G.; Pollard, M.; Gouveia, J.P.; Giannakidis, G.
Abstract: The European Commission has acknowledged the significance of local and regional communities in its effort to tackle climate change. In this respect a number of initiatives and programmes (e.g. Covenant of Mayors, Covenant of Mayors for Climate and Energy, CONCERTO, CIVITAS, etc.) have been set up in order to engage European cities in the effort towards a low carbon future and an improved quality of life through sustainable economic development. These initiatives have been generally successful and have resulted in the commitment of an increasing number of European cities towards sustainable development goals. At the same time, however, it has been revealed that there is a critical need for improved comprehensive city planning driven by an integrated and strategic approach, focused on cost benefit assessment towards sustainable energy use. This paper presents an innovative city planning approach developed within the EU FP7 project InSMART. It brings together four European municipalities – Evora (Portugal), Nottingham (UK), Trikala (Greece) and Cesena (Italy) –, academics, industries and technical consultants in order to establish a common methodology for enhancing sustainable planning for both the current and future city needs through an integrative and multidisciplinary approach. The methodology develops and employs a number of tools to assess the optimum mix of medium term measures (up to 2030) for a sustainable energy future, addressing the efficiency of energy flows across various city sectors with regards to economic, environmental and social criteria and paving the way towards actual implementation of priority actions. This paper presents the key concepts around this methodology and some selected results of the project (still ongoing). The results refer to the four city partners, all actively involved in developing a more sustainable energy system. Further on, the proposed approach may be replicable to other cities.